Community sport organizations, regional governance, and sport policy implementation in Ontario, Canada - Kyle A. Rich; Dante Losardo (Frontiers in Sports and Active Living)
Within multi-level sport governance systems, community sport organizations (CSOs) can be understood as implementers of sport policy. In Canada, extensive research exists examining governance at the national level, and the managerial implications for clubs at the community level. However, there is a dearth of research on the role of governance/policy at the regional level. In this brief research report, we examine the role of CSOs as implementers of sport policy in Ontario, Canada. We used a case study methodology to answer two research questions: (1) How do actors from CSO's in Ontario understand their roles in developing sport participation opportunities? and, (2) How do CSOs’ institutional and community contexts shape organizational practices and the translation of ideas within sport development? We collected data through semi-structured interviews with 12 managers of CSOs affiliated with the same sport/provincial sport organization. Data were analyzed using thematic analysis. Findings indicate that CSOs have limited capacity for adaptation or change and that they experience powerful external pressures and competing demands. This research provides empirical insight into sport policy implementation processes in Ontario and highlights the importance of facility access as well as policy from other organizations/institutions (particularly municipalities and school boards) in shaping CSO practices.